Potensi Daerah Sidik Jari Spektrum Inframerah Sebagai Penanda Bioaktovitas Ekstrak Tanaman Obat - Latifah Kosim Darusman; Rudi Heryanto; Mohamad Rafi; Wulan Tri Wahyuni (Institut Pertanian Bogor, 2007)
Efficacy and quality of medicinal plant extracts depend on chemical composition therein. Therefore, to ensure its efficacy orquality, the chemical composition of extracts have to be analyzed based on its chemical marker or its chemical pattern. This study tried to develop a method for extracts quality assay based on infrared spectrum in fingerprint region and extracts inhibition activity to xanthine oxidase. Five extracts from kunyit (Curcuma domestica), temulawak ( C xanthorriza), jahe (Zingiber officina/e), temukunci (Boesenbergia pandurata), and cabe jawa (Piper retrofractum) were tested to inhibit xanthine oxidase activity. The bioactive data of extracts and its infrared spectrum was analyzed using PCA and PLS-DA (partial least squarediscriminant analysis). Almost all extracts that were tested showed inhibition activity to xanthine oxidase activity, except the extract of jahe. The result showed that PCA can group all of extract into each of their region. Meanwhile, PLS-DA has shown to be a good prediction model for classifying extracts based on fingerprint region of its mR Spectrum and its biological activity. Keywords: fingerprint, mR spectra, compound marker, xanthine oxidase